Anti-Psoriatic Efficacies of Psorogrit and Divya-Taila, in Murine Models of Imiquimod and TPA-Induced Psoriasis-Like Inflammation are Driven by Modulation in IL-17RA/IL-23 and IL-8/TNF-α Signaling Axes - Balkrishna A; Sharma S; Dey T; Maity M; Shukla S; Kumari A; Tomer M; Dev R; Sinha S; Varshney A (Journal of Inflammation Research)
Acharya Balkrishna,1– 4 Sonam Sharma,1 Tapan Dey,1 Madhulina Maity,1 Sunil Shukla,1 Ankita Kumari,1 Meenu Tomer,1 Rishabh Dev,1 Sandeep Sinha,1 Anurag Varshney1,2,5 1Drug Discovery and Development Division, Patanjali Research Foundation, Governed by Patanjali Research Foundation Trust, Haridwar, Uttarakhand, India; 2Department of Allied and Applied Sciences, University of Patanjali, Patanjali Yog Peeth, Haridwar, Uttarakhand, India; 3Patanjali Yog Peeth (UK) Trust Kinning Park, Glasgow, UK; 4Patanjali Yogpeeth Nepal, Budhanilkantha Metropolitan, Kathmandu, Nepal; 5Special Centre for Systems Medicine, Jawaharlal Nehru University, New Delhi, IndiaCorrespondence: Anurag Varshney, Drug Discovery and Development Division, Patanjali Research Foundation, Governed by Patanjali Research Foundation Trust, Haridwar, Uttarakhand, India, Email anurag@patanjali.res.inAim: Psoriasis is a chronic inflammatory skin disease that occurs among all age groups, irrespective of gender, and consequently it negatively impacts patient’s quality of life. Medicines of herbo-mineral origin are being increasingly used for the mitigation of psoriasis, due to the side effects associated with the available treatment options. Present study characterizes the pharmacological efficacy of Psorogrit (PSO) and Divya-Taila (DT) using in vitro and in vivo assays.Methods: Human keratinocyte (HaCaT) cells stimulated with TNF-α or Imiquimod (IMQ) were used to generate the in vitro models of psoriasis. PSO was further evaluated for modulation of mRNA expression, cytokine levels and NF-κB reporter activity. The in vivo anti-psoriatic activity of the orally given PSO and topically applied DT was assessed in mouse models of IMQ-induced psoriasis-like skin lesions and 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced ear edema. The animals were randomly allocated to the Normal control, Disease control, Clobetasol, PSO and DT groups. Analysis of ear thickness, ear punch weight, spleen weight, histopathology by hematoxylin and eosin (H&E), and Keratin 17 (KRT 17) mRNA expression was measured for evaluation of these herbal formulations. Moreover, the phytochemical composition of PSO and DT was evaluated by UHPLC and GC/MS/MS.Results: Cytosafe concentrations of PSO significantly attenuated IL-8 release as well as mRNA expressions of IL-8, TNF-α, and IL-1β in TNF-α-induced human skin keratinocytes. PSO was observed to decrease the TNF-α-induced NF-κB reporter activity. Additionally, in IMQ-induced HaCaT cells, PSO reduced the release of IL-17RA and mRNA expression of IL-23 and IL-17RA. In the in vivo IMQ-induced model, PSO and DT were able to ameliorate the IMQ-induced increase in ear punch weight, relative spleen weight, and histopathological changes in both ear and dorsal back skin. In TPA-induced ear edema model, PSO and DT reduced the increase in ear thickness, ear punch weight, and histopathological lesions. Besides, the phytochemical analysis of PSO and DT revealed the presence of phytometabolites known to have anti-inflammatory activities.Conclusion: The combinatorial use of Psorogrit and Divya-Taila has the potential to ameliorate clinical and pathological manifestations of psoriasis.Keywords: cytokine, Divya-Taila, imiquimod, IL-17RA, NF-κB, psoriasis, Psorogrit, TPA